Identification of Key Gene Networks Associated With Cell Wall Components Leading to Flesh Firmness in Watermelon - Anees, Muhammad; Gao, Lei; Umer, Muhammad Jawad; Yuan, Pingli; Zhu, Hongju; Lu, Xuqiang; He, Nan; Gong, Chengsheng; Kaseb, Mohamed Omar; Zhao, Shengjie; Liu, Wenge (Frontiers in Plant Science, 2021)
Flesh firmness of watermelon is an important quality trait for commercial fruit values, including fruit storability, transportability, and shelf life. To date, knowledge of the gene networks underlying this trait is still limited. Herein, we used weighted genes co-expression network analysis (WGCNA) based on correlation and the association of phenotypic data (cell wall contents) with significantly differentially expressed genes between two materials, a near isogeneic line “HWF” (with high average flesh firmness) and inbred line “203Z” (with low average flesh firmness), to identify the gene networks responsible for changes in fruit flesh firmness. We identified three gene modules harboring 354 genes; these gene modules demonstrated significant correlation with water-soluble pectin, cellulose, hemicellulose, and protopectin. Based on intramodular significance, eight genes involved in cell wall biosynthesis and ethylene pathway are identified as hub genes within these modules. Among these genes, two genes, Cla012351 (Cellulose synthase) and Cla004251 (Pectinesterase), were significantly correlated with cellulose (r2 = 0.83) and protopectin (r2 = 0.81); three genes, Cla004120 (ERF1), Cla009966 (Cellulose synthase), and Cla006648 (Galactosyltransferase), had a significant correlation with water-soluble pectin (r2 = 0.91), cellulose (r2 = 0.9), and protopectin (r2 = 0.92); and three genes, Cla007092 (ERF2a), Cla004119 (probable glycosyltransferase), and Cla018816 (Xyloglucan endotransglucosylase/hydrolase), were correlated with hemicellulose (r2 = 0.85), cellulose (r2 = 0.8), and protopectin (r2 = 0.8). This study generated important insights of biosynthesis of a cell wall structure and ethylene signaling transduction pathway, the mechanism controlling the flesh firmness changes in watermelon, which provide a significant source to accelerate future functional analysis in watermelon to facilitate crop improvement.